Do Tuition Fees Crowd Out Donations for Religious Public Goods? - Hendri, Davy (Share: Jurnal Ekonomi dan Keuangan Islam, 2024)
The provision of public goods, particularly religious educational facilities like Al-Qur’an Learning Center (Taman Pendidikan Al-Qur’an - TPA), often faces financial constraints due to their reliance on voluntary donations. To address funding gaps, some institutions have adopted a hybrid model that combines voluntary donations with mandatory tuition fees. This study investigates the impact of introducing tuition fees on donation amounts and the perceived utility of TPA services among residents in Padang City, West Sumatra, Indonesia. Using Ordinary Least Squares (OLS) regression analysis on data from 600 households across 30 housing estates, the research examines the relationship between tuition fees, voluntary donations, and the perceived utility of TPA services. Utilizing the Lancastrian model, the study reveals an inverse U-shaped relationship between donations and perceived utility. While increased tuition fees initially correlate with a perceived improvement in TPA services or infrastructure, likely due to an association between higher fees and quality, this effect diminishes as fees continue to rise. This suggests that while residents may accept and even welcome reasonable fees, excessive charges can discourage voluntary donations, even if individuals remain intrinsically motivated to support the TPA. These findings highlight the importance of carefully balancing financial sustainability with community engagement in TPA funding models. Striking this balance is essential to ensure the continued success and community support of these important institutions.========================================================================================================ABSTRAK – Apakah Pengenaan Biaya untuk Fasilitas Keagamaan Publik mengurangi Donasi? Pengelolaan fasilitas publik, terutama dalam pendidikan keagamaan seperti Taman Pendidikan Al-Qur'an (TPA), seringkali mengalami kendala keuangan. Sumber pendanaan yang hanya mengandalkan sumbangan masyarakat menjadi kendala utama. Untuk mengatasi hal tersebut, beberapa lembaga pendidikan mengadopsi model pembiayaan gabungan antara sumbangan sukarela dengan biaya wajib. Studi ini mengkaji dampak pembebanan biaya pendidikan terhadap jumlah sumbangan dan manfaat yang dirasakan dari TPA di kalangan penduduk Kota Padang, Sumatera Barat, Indonesia. Penelitian ini melibatkan 600 rumah tangga di 30 kompleks perumahan. Melalui analisis regresi Ordinary Least Squares (OLS), studi ini mengkaji hubungan antara biaya pendidikan, sumbangan sukarela, dan manfaat yang dirasakan dari TPA. Dengan menggunakan model Lancastrian, studi ini menemukan hubungan berbentuk U terbalik antara sumbangan dan utilitas yang dirasakan. Meskipun pembebanan biaya pendidikan berkorelasi positif dengan peningkatan layanan atau infrastruktur TPA, hal ini akan berkurang seiring dengan meningkatnya biaya. Artinya, masyarakat pada dasarnya menerima pembebanan biaya pendidikan yang wajar. Namun, pembebanan biaya yang dianggap berlebihan dapat mengurangi sumbangan sukarela, meskipun mereka secara intrinsik tetap mendukung keberlangsungan TPA. Temuan ini menekankan pentingnya model pendanaan yang dapat menyeimbangkan keberlanjutan finansial dengan keterlibatan masyarakat. Model pendanaan yang ideal akan menjamin kesuksesan lembaga ini, sekaligus menjaga dukungan masyarakat yang berkelanjutan.